2005
DOI: 10.1080/00218460590904444
|View full text |Cite
|
Sign up to set email alerts
|

Critical and Subcritical Adhesion Measurements of a Model Epoxy Coating Exposed to Moisture Using the Shaft-Loaded Blister Test

Abstract: The shaft-loaded blister test (SLBT) was used to investigate the adhesion between a model epoxy coating and a silicon oxide surface as a function of relative humidity. Critical and subcritical strain energy release rates were measured using specimens that incorporate reinforcing layers of Kapton 1 film. A simplified procedure that eliminates the need for video imaging to measure the blister radius and fracture energy was developed. A critical relative humidity level for adhesion loss was observed, in agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…This result has been discussed but is nowadays largely confirmed [41]. The explanation is that below 70% RH water remains in the polymeric networks and that above this value it condenses at the interface.…”
Section: Relative Humiditysupporting
confidence: 49%
“…This result has been discussed but is nowadays largely confirmed [41]. The explanation is that below 70% RH water remains in the polymeric networks and that above this value it condenses at the interface.…”
Section: Relative Humiditysupporting
confidence: 49%
“…During the fracture tests, the samples were exposed to (a) deionized (DI) water, (b) aqueous 0.1 mol/L sodium chloride (NaCl), or (c) saturated (6.1 mol/L) NaCl solution. A similar protocol to that reported by O'Brien et al was used for assessing the impact of environmental factors on adhesion. For comparison, a “control” experiment in air was also conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work suggested that the load-based equation is the preferred expression to calculate G due to the reduced effects of plastic deformation at the contact area and the insensitivity to changes in mechanical properties of the film [16,24] due to plasticization by fluid absorption. [23] However, in the presence of the slip-stick failure as observed for these samples, the displacement-based is the most appropriate expression to calculate G. Specimens were tested using loading and unloading cycles, which were repeated multiple times, to determine the crack length as a function of load and displacement (blister height). The uncertainty due to sample-to-sample variation is always equal to or greater than the uncertainty introduced by measuring the blister radius.…”
Section: Methodsmentioning
confidence: 99%
“…NR has been used to quantify the moisture content at the polymer/substrate interface for a series of substrate surfaces. The shaft-loaded blister test (SLBT) has been utilized to measure adhesion [16][17][18][19][20][21][22][23][24] and mechanical properties of the adhered thin films. [16,20,[25][26][27][28][29][30] Using neutron reflectivity and SLBT adhesion measurements, we investigate how surface chemistry influences the water content near the interface and the adhesive fracture energy after attaining an apparent equilibrium in either the dry (0 % relative humidity (rh.)…”
mentioning
confidence: 99%